Adherence among parents on under-five childhood immunization schedule: a review - Mohd Zulkefli, Nor Afiah; Rusli, Mohammad Farhan; Juni, Muhamad Hanafiah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Background: Adherence on under-five childhood immunization schedule has been an area of study that has seldom been explored. Adherence has been the subject of focus in determine if the results of outbreaks and vaccine preventable disease is related to the adherence of the parents to the vaccine schedule.